Do investments in flexibility enhance sustainability? A simulative study considering the German electricity sector. Issue 11 (20th August 2020) - Schäfer, Pascal; Daun, Torben M.; Mitsos, Alexander
Abstract: Current research concerning industrial demand side management primarily focuses on monetary aspects. Herein, we extend this perspective by assessing whether economically driven measures increasing the flexibility also result in reduced contributions to the residual load. For this purpose, we conduct a simulative study using historic and projected time series for the German electricity sector. First, Fourier analysis are performed to show that the main oscillation in the electricity price time series has a period length of 12 hr, whereas the renewable generation is primarily characterized by an oscillation with a period length of 24 hr. Second, a generic process model with capabilities for load shiftings is used to evaluate how the fluctuation patterns can be exploited via scheduling optimizations. Most importantly, our results demonstrate that prevalent price fluctuations prevent adequate monetary incentives for providing storage capacities for bridging up to 24 hr, which are desired for reducing the residual load.